Perspective of Justice among Advocates of Rape Victims - Mutia Husna Avezahra; Koentjoro Koentjoro (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Rape cases involve various factors and perspectives. This study explored factors in constructing the perspective of justice among advocates of rape victims in Malang, East Java. This study adopted the qualitative phenomenology approach with semi-structured in-depth interview for data collection, and thematic analysis as the data analysis technique. The participants of this study were six advocates from two different women support groups and two experts, one was a Law lecturer and an investigator in the Woman and Children Service Unit (Unit Pelayanan Perempuan dan Anak) (UPPA) at Malang Police Department. The result revealed that justice perspectives of advocates were mainly rooted in the feminist concept at their ideological level; and therefore, the perceived meaning of justice tend to be idealistic and participants were rather dissatisfied with the existing legal system. Participants further expressed their self-interest to advocate based on the shared gender identity as women with the rape victims. As such, findings of this study might inform the evaluation of prevailing procedure and the substances of law enforcement leading to accommodating the needs of rape victims.